Indonesian higher education students’ perception on critical literacy - Hardianti, Meisela (Englisia: Journal of Language, Education, and Humanities, 2024)
Critical literacy is a crucial aspect of education that empowers individuals to analyse, interpret, and evaluate texts critically. Despite its significance, the integration of critical literacy in the Indonesian higher education system remains limited. This study aims to bridge this gap by examining the perceptions of Indonesian higher education students about critical literacy. The research question guiding this study is: What are the perceptions of Indonesian higher education students regarding critical literacy and its importance in the context of their academic and professional development? The study employs a qualitative research design using the single-case study method. Data collection is conducted through interviews, and the data is analysed using case study analysis techniques. The study takes place in an English language education program at a private university in Yogyakarta, Indonesia, which prioritises critical literacy in its curriculum. The findings of this study contributed to the understanding of how Indonesian higher education students perceive and engage with critical literacy and inform strategies to promote critical literacy skills among students. Ultimately, it aims to cultivate a generation of critically literate individuals who can actively engage in social, cultural, and professional contexts, contributing to the development of a knowledgeable and empowered society.